Legalitas Pemanfaatan Open Source Intelligence oleh Direktorat Jenderal Pajak Dalam Penggalian Potensi dan Pengawasan Wajib Pajak - Muchammad Rochandi Alif; Agus Ariadi (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
Over the past three years, tax revenue in Indonesia has faced significant structural challenges, largely driven by the expansion of the shadow economy and insufficient voluntary compliance among digital business operators. In response, the Directorate General of Taxes has leveraged Open Source Intelligence as a strategic tool for tax potential mapping and taxpayer oversight, particularly within the e-commerce and social media landscape. This study examines the operational legality of Open Source Intelligence usage under Indonesian positive law, alongside the judicial boundaries dictated by the principle of legality and personal data protection frameworks. Employing a normative juridical method, this research finds that the use of Open Source Intelligence is firmly grounded in Article 35A of the Law on General Provisions and Tax Procedures, in conjunction with Directorate General of Taxes Regulation No. PER-15/PJ/2019. To ensure legal certainty and compliance with Law No. 27 of 2022 on Personal Data Protection, the DGT must establish rigorous standard operating procedures for public electronic data collection, thereby preventing constitutional privacy infringements. Ultimately, this research proposes the harmonization of DGT’s internal regulations with national data protection laws to balance the state’s fiscal interests with the preservation of civil rights.